PERFORMANCE MEASUREMENT OF BAZNAS USING THE MASLAHAH PERFORMANCE (MaP) APPROACH - Arief Masturo (Department Islamic Economics, 2025)
Indonesia has enormous zakat potential, and BAZNAS, as the official government institution, plays a strategic role in the collection, management, and distribution of zakat. This study aims to measure the performance of the National Amil Zakat Agency (BAZNAS) using the Maslahah Performance (MaP) approach, which is based on maqashid shariah. The research method used is qualitative, through in-depth interviews, document analysis, and internal BAZNAS data processing. The MaP approach covers six orientations: worship, internal processes, talent, learning, donors (muzaki), and wealth. The results show that BAZNAS achieved a score of 1.000 in both process and outcome performance aspects, which means maximum performance and optimal maslahah have been achieved. These findings confirm the effectiveness of MaP as a performance measurement tool for zakat organizations.